Arabic Language Learning Restoration in Overcoming the Crisis of Ulama in UIN Satu Tulungagung - Ahmad Nurcholis; Heru Arif Pianto; Timbul; Muhamad Asngad Rudisunhaji (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study uses a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, observation, and document analysis. The grand theory used is the hermeneutic theory proposed by Gadamer which emphasizes that the educational horizon someone has in the present is formed as an accumulation of various cadre formations in the past in a continuous circular motion. The results of the study show that, first, there is a focus on producing cleric cadres through the Hadith Studies Program, enabling them to understand and read classical Islamic texts (kitab kuning). Second, a curriculum for Hadith studies based on Turats is designed to develop a moderate and tolerant interpretation of Islam with a Nusantara perspective. Third, there is a Tahfidz Hadith Scholarship, with the requirement of passing an exam in reading classical texts (kitab kuning). Fourth, there is a Hadith memorization program through a Hadith Studies Boarding School quarantine. Fifth, ulama from Egypt are invited to teach, using Arabic as the language of instruction. This study concludes that the restoration of Arabic language learning can be an effective solution in addressing the cleric crisis at UIN Satu Tulungagung.